2013
DOI: 10.1007/s00213-013-3008-x
|View full text |Cite
|
Sign up to set email alerts
|

Excessive aggression as model of violence: a critical evaluation of current preclinical methods

Abstract: Rationale Preclinical experimental models of pathological aggressive behavior are a sorely understudied and difficult research area. Objectives How valid, reliable, productive and informative are the most frequently used animal models of excessive aggressive behavior? Methods The rationale, key methodological features, supporting data and arguments as well as their disadvantages and limitations of the most frequently used animal models for excessive aggressive behavior are summarized and their validity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 89 publications
4
70
0
7
Order By: Relevance
“…Classically, RI consists of placing an intruder male conspecific in the home cage of the resident animal and observing subsequent aggressive behavior. This paradigm has been extensively used in species from fish to flies to rodents (Miczek et al 2013). When RI is repeated over multiple days, the probability of winning a fight increases with each successive victory (Oyegbile and Marler 2005, Schwartzer et al 2013).…”
Section: Figurementioning
confidence: 99%
“…Classically, RI consists of placing an intruder male conspecific in the home cage of the resident animal and observing subsequent aggressive behavior. This paradigm has been extensively used in species from fish to flies to rodents (Miczek et al 2013). When RI is repeated over multiple days, the probability of winning a fight increases with each successive victory (Oyegbile and Marler 2005, Schwartzer et al 2013).…”
Section: Figurementioning
confidence: 99%
“…So far, the neural underpinnings of alcohol-induced aggression have mainly been studied in animal models of excessive aggression (eg, resident-intruder paradigms), which might not be representative for humans (Miczek et al, 2013). To the best of our knowledge, the present study investigates for the first time the neural mechanisms of alcohol-induced human aggression in relation to provocation at moderate alcohol intoxication (breath alcohol concentration (BrAC) = 0.6 g/kg).…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed two laboratory models that mimic important characteristics of affective/reactive and instrumental/proactive forms of aggression, and proposed behavioral methods to differentiate species-typical and abnormal forms of aggression [17][18][19][20]. Importantly for the present study, we found that rats submitted to one of these models -the glucocorticoid dysfunction model of abnormal aggression-deliver bites to vulnerable body parts of conspecifics (head, throat and belly), which is accompanied by low intention signaling by threats, disturbed social behavior, and reduced autonomic arousal, features that are in many respects to similar to the symptoms of aggressive antisocial personality disordered subjects [17][18][19][20]. We found that in this model, aggressive encounters increase the activation of the lateral hypothalamus, central amygdala and ventral periaqueductal grey (PAG) above the levels seen in controls submitted to fights (i.e.…”
Section: Introductionmentioning
confidence: 99%